ANALYSIS OF ACCOUNTING UNDERSTANDING LEVEL AND READINESS LEVEL FOR IMPLEMENTATION OF SAK EMKM IN CLOTHING MSMEs, IN DEPOK - Mufid Suryani; Rio Eka Syahputra (Asosiasi Dosen Muda Indonesia, 2022)
Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM) are financial accounting standards specifically designed as financial accounting standards for MSMEs or entities that have not been able to meet the accounting requirements stipulated in SAK ETAP with the aim of facilitating financial reporting needs and as a reference for decision making . This study aims to determine and analyze the level of understanding of accounting and the level of readiness of MSME players for the Implementation of SAK EMKM, which can increase people's competitiveness. This study uses primary data on clothing sellers in the Tugu Village, Cimanggis District, Depok City using a purposive sampling technique. The results showed that the level of accounting understanding of MSME actors regarding the implementation of SAK EMKM in the clothing sales business in Tugu Village, Cimanggis District, Depok City using the help of a questionnaire was high. While the level of readiness of MSME actors for the Implementation of SAK EMKM is Adequate or Lacks Understanding.